A Chronic fatigue syndrome model demonstrates mechanical allodynia and muscular hyperalgesia via spinal microglial activation. Issue 9 (23rd May 2014) - Yasui, Masaya; Yoshimura, Takashi; Takeuchi, So; Tokizane, Kyohei; Tsuda, Makoto; Inoue, Kazuhide; Kiyama, Hiroshi
<x xml:space="preserve">Abstract</x> Patients with chronic fatigue syndrome (CFS) and fibromyalgia syndrome (FMS) display multiple symptoms, such as chronic widespread pain, fatigue, sleep disturbance, and cognitive dysfunction. Abnormal pain sensation may be the most serious of these symptoms; however, its pathophysiology remains unknown. To provide insights into the molecular basis underlying abnormal pain in CFS and FMS, we used a multiple continuous stress (CS) model in rats, which were housed in a cage with a low level of water (1.5 cm in depth). The von Frey and Randall–Seritto tests were used to evaluate pain levels. Results showed that mechanical allodynia at plantar skin and mechanical hyperalgesia at the anterior tibialis (i.e., muscle pain) were induced by CS loading. Moreover, no signs of inflammation and injury incidents were observed in both the plantar skin and leg muscles. However, microglial accumulation and activation were observed in L4–L6 dorsal horn of CS rats. Quantification analysis revealed a higher accumulation of microglia in the medial part of Layers I–IV of the dorsal horn. To evaluate an implication of microglia in pain, minocycline was intrathecally administrated (via an osmotic pump). Minocycline significantly attenuated CS‐induced mechanical hyperalgesia and allodynia. These results indicated that activated microglia were involved in the development of abnormal pain in CS animals, suggesting that the pain observed in CFS and FMS patients may be partly caused by a mechanism in which microglial activation is involved. GLIA 2014;62:1407–1417